Peluang Dan Tantangan Pembelajaran Daring Pada Masa Pandemi Covid-19 Dalam Perspektif Mahasiswa - Wujarso, Riyanto; Saprudin, Saprudin (Journal of Information System, Applied, Management, Accounting and Research, 2021)
The almost two-year-long Covid-19 epidemic has altered the world order. This illness affects many spheres of life, including education. The government has a policy of restricting activities that involve direct human interaction. Learning that was previously conducted face-to-face in schools and on campuses is now conducted remotely, or through what is commonly referred to as online learning. This is done specifically to prevent and reduce the spread of the Covid-19 virus. The purpose of this study is to determine the advantages and disadvantages of online learning from the perspective of students. The study employed descriptive quantitative techniques on a sample of 253 STIE Jayakarta Jakarta students. The findings indicated that the majority of students attended online lectures from their homes, with the majority residing in Jabodetabek. Online education makes it easier to comprehend information and learning materials because the majority of these students are millennials who are already familiar with technology. However, the results of this study indicated that the majority of students believed that online learning was no better than offline or face-to-face instruction.